Who is to judge? : the perennial debate over whether to elect or appoint America's judges - Geyh, Charles Gardner (New York, NY : Oxford University Press, 2019)
'Who is to Judge?' tackles the judicial selection debate head on. Judicial politics expert Charles Gardner Geyh exposes the exaggerations of binary arguments in support of either elective or appointive systems, approaching middle ground and ultimately arguing that no single system of selection is optimal for all jurisdictions at all times.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 8, 2019).
Keywords: Judges -- Selection and appointment -- United States; Law; Laws of specific jurisdictions & specific areas of law